THE ROLE OF POLITICAL PARTIES TO IMPROVE WOMEN REPRESENTATION IN PARLIAMENT OF THE REPUBLIC OF INDONESIA AND LOCAL LEGISLATIVE - Aisah Putri Budiatri (Pusbindiklat - LIPI, 2012)
Until now, the highest level of women representation in Indonesian parliament is 18%, obtained from theelection in 2009. Political party as the only formal political instrument that is recognized by law has an importantrole to solve the problem. The study, which is based on Anne Phillips and Burnheim’s theory of political representation,found that political parties have a low commitment to involve women in party’s structure and electoralprocess. By using qualitative research methods, the study found that the role of parties in the political process hasnot been used optimally to improve the representation of women in parliament.